2023
DOI: 10.1002/anie.202304475
|View full text |Cite
|
Sign up to set email alerts
|

Atroposelective Silylation of 1,1′‐Biaryl‐2,6‐diols by a Chiral Counteranion Directed Desymmetrization Enhanced by a Subsequent Kinetic Resolution

Abstract: A desymmetrizing silylation of aromatic diols is reported. The previously unknown asymmetric silyl ether formation of phenol derivatives is achieved by applying List's counteranion directed silylation technique. A silylium-ion-like silicon electrophile generated from an allylic silane paired with an imidodiphosphorimidate (IDPi) enables enantioselective discrimination of achiral 1,1'-biaryl-2,6-diols. The enantioselectivity of that desymmetrization is further improved by a downstream kinetic resolution, conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A catalyst evaluation showed popular IDPi’s to provide insufficient enantioselectivities while our sterically bulky IDPi provided encouraging results (Table entries 1–10). In more detail, catalyst structures 2b , , 2c , 2d , , 2e , 2g , 2h , 2i , 2j have all proved to be valuable in generating a diverse range of chiral compounds with high-levels of stereoselectivity. Ultimately, most of these catalysts has been confirmed to be optimal for at least one reaction type rendering these structures as important benchmarks for evaluating 2a in this reaction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A catalyst evaluation showed popular IDPi’s to provide insufficient enantioselectivities while our sterically bulky IDPi provided encouraging results (Table entries 1–10). In more detail, catalyst structures 2b , , 2c , 2d , , 2e , 2g , 2h , 2i , 2j have all proved to be valuable in generating a diverse range of chiral compounds with high-levels of stereoselectivity. Ultimately, most of these catalysts has been confirmed to be optimal for at least one reaction type rendering these structures as important benchmarks for evaluating 2a in this reaction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…11 12 Thereafter, several groups have reported silylative enantioselective desymmetrization of meso -1,2-diols by using scaffolding catalysts and silyl chlorides, 13 BINOL-based polyether catalyst and hexamethyldisilazane (HDMS), 14 and silylative enantioselective desymmetrization of 1,1′-biaryl-2,6-diols by using Brønsted acid catalyst and HDMS, 15 and Brønsted acid catalyst and allylic silane. 16 17…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…During our studies, Professor Martin Oestreich kindly shared a manuscript with us describing his independent and advanced investigation of the same transformation. 10 Our own studies on the asymmetric silylation of biaryl diols have since been terminated at the reported stage.…”
Section: Scheme 3 Control Experimentsmentioning
confidence: 99%